Menggagas Arah Pendidikan Berbasis Prinsip Universal - Sudarmaji, Agus (Sukma: Jurnal Pendidikan, 2024)
This study explores the application of universal principles in education to address challenges in multicultural contexts. Through a mixed-methods approach, data were collected via surveys and interviews with educators across various regions. The findings reveal that integrating universal principles into the curriculum enhances both student engagement and learning outcomes. The research contributes to the discourse on education reform by offering a scalable framework adaptable to diverse educational settings.